Sensory Augmentation for a Rapid Motor Task in a Multisensory Environment - Negen, J.; Slater, H.; Nardini, M. (Restorative Neurology and Neuroscience, 2024)
Background: Sensory substitution and augmentation systems (SSASy) seek to either replace or enhance existing sensory skills by providing a new route to access information about the world. Tests of such systems have largely been limited to untimed, unisensory tasks. Objective: To test the use of a SSASy for rapid, ballistic motor actions in a multisensory environment. Methods: Participants played a stripped-down version of air hockey in virtual reality with motion controls (Oculus Touch). They were trained to use a simple SASSy (novel audio cue) for the puck’s location. They were tested on ability to strike an oncoming puck with the SASSy, degraded vision, or both. Results: Participants coordinated vision and the SSASy to strike the target with their hand more consistently than with the best single cue alone, t(13) = 9.16, p < .001, Cohen’s d = 2.448. Conclusions: People can adapt flexibly to using a SSASy in tasks that require tightly timed, precise, and rapid body movements. SSASys can augment and coordinate with existing sensorimotor skills rather than being limited to replacement use cases – in particular, there is potential scope for treating moderate vision loss. These findings point to the potential for augmenting human abilities, not only for static perceptual judgments, but in rapid and demanding perceptual-motor tasks.
EPrint Processing Status: Full text deposited in DRO, closed access